Concentric Perfect Optical Vortex Beam Generated by a Digital Micromirrors Device - Ziqiang Xin; Chonglei Zhang; Xiaocong Yuan (IEEE Photonics Journal)
We propose a kind of perfect optical vortex beam (POV) generated via Fourier transformation of Bessel-Gauss (BG) beams through encoding of the amplitude of the optical field with binary amplitude digital micromirrors device. We call them concentric POVs which consist of several POVs and where every POV has the same center and independent characters, and we confirm the correct phase patterns of the concentric POVs with the method of Mach–Zehnder interference and self-interference. This special property could be considered as a potential of implement to increase the orbital angular momentum communication capacity vastly.